From Private Problem to Institutional Agenda: Applying Anderson’s Model to the Decline of Student Enrollment in Private Vocational Schools - Tjipto Suharsoyo; Mufarrihul Hazin; Budi Purwoko (Sustainable Human Capital Development Journal, 2025)
This study investigates the educational policy process in response to the decline in new student enrollment at Private Vocational High Schools (SMKS) in Mojokerto Regency and City for the 2025-2026 Academic Year. Utilizing Anderson's Public Policy theory, it traces the issue's evolution from an internal problem to an institutional one. Data were collected through document analysis, structured interviews with school principals and local education office officials, and policy observation. The findings reveal that the decline, initially an internal issue of attractiveness and competition, escalated into a public problem as it affected 35% of private SMKs. It further transformed into a systemic Education Policy Issue upon the discovery of an imbalanced quota allocation, where public schools accommodated only 38% of junior high school graduates, creating inequity for private SMKs. The issue was elevated to the institutional agenda through interventions such as reviewing admission quotas, advocating for fairer zoning, and enhancing collaboration with the Business and Industrial World (DUDI). The study concludes that Anderson's model provides an effective framework for understanding education policy dynamics in crisis response and underscores the need for inclusive policies to ensure the sustainability of private vocational education. These findings offer practical contributions for policymakers in designing more responsive and sustainable interventions